Socioeconomic Determinants of Online Impulse Buying Behavior in Metropolitan India: A Comparative Study Across E-Commerce Platforms - Rahul Joshi, Forum (Digital Repository of Theses, 2026)
Even though e-commerce is rapidly expanding in India, particularly in the metropolitan areas of today like Delhi, Mumbai, Bengaluru, Chennai, and Hyderabad, little is known about how the socioeconomic traits influence online impulse buying behaviours in various online channels. This study aims to explore the effects of socioeconomic variables on online impulse purchasing behaviour among consumers in metropolitan India and to determine the level of differences in how these variables impact motivation different online e-commerce websites. The existing study research questions are: Which are the most critical socioeconomic factors that can predict online impulse buying behaviour of consumers in metropolitan India?; Which are the significant challenges by various socioeconomic categories of individuals in regulating or controlling the capacity of online impulse purchasing through the online shopping systems in metropolitan India?; What do e-commerce platforms have to exploit opportunities so that they can capture more of the diverse socioeconomic groups and keep the adverse impact of impulse buying at a minimum?; What are the recommendations that can be given to e-commerce sites to lead to responsible marketing that deals with socioeconomic diversity in metropolitan India? There are three cities namely, Bangalore, Delhi and Hyderabad taken for survey. Therefore, Bangalore, Delhi and Hyderabad are universe for current research. Name of the E-commerce companies selected for study are Amazon, Flipkart, Myntra, Meesho. In this study respondents are randomly selected using purposive sampling techniques. Sample size for the study includes 600 customers buying products from Amazon, Flipkart, Myntra, Meesho. The study investigated the factors influencing online impulse buying behaviour among consumers in metropolitan India and examined strategies to mitigate such behaviour. The demographic analysis revealed that consumers from diverse age groups, income levels, educational backgrounds, occupations, and marital statuses engage in impulse buying, with younger individuals, students, and those with higher disposable incomes showing higher susceptibility. Gender, household composition, and access to credit also emerged as significant contributors to impulsive purchasing behaviour. The socioeconomic factors highlighted that lack of financial literacy, limited digital skills, exposure to advertisements, peer influence, lifestyle, and device quality significantly affect online impulse buying. Keywords: Behavior, E-Commerce Platforms, Online Impulse Buying, Metropolitan, Socioeconomic